The impact of state audit work on the level of political parties’ transparency: a case study of Croatian political parties - Čular, Marko (Oeconomica Jadertina, 2022)
The work of the state audit is of key interest to the public because state auditors audit the entities that are mostly financed from the state budget. Given that one of the main goals of state auditors is to increase transparency and more efficient spending of budget funds, state audit is an integral part of any democratic system. The truthfulness and credibility of the financial statements and the consistency of the operations of political parties, which is confirmed by state auditors, are certainly one of the leading interests of the public eye. The State Audit Office, as the supreme audit institution in Croatia, is obliged to conduct an audit of political parties for those with an income of more than HRK 100,000. This research is focused on the analysis of the work of the state audit on political parties for 2019, which includes 20 parliamentary and 24 non-parliamentary political parties. The subject of the state audit was the financial statements and the compliance of the operations of political parties. The analysis of individual state audit reports on the work of political parties revealed numerous irregularities in the area of scope and internal organization, internal control system, planning, accounting, financial statements, revenues, expenditures, assets, liabilities and own resources, and prohibition of financing and favouritism. State auditors gave a qualified opinion to 39%of political parties. Recommendations and directions given by state auditors from previous periods have shown that political parties implement the given recommendations to a greater extent and that the work of the state audit affects the transparency of political parties.
Keywords: state audit; political parties; transparency